2021
DOI: 10.1161/strokeaha.120.033595
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index in 1.9 Million Adolescents and Stroke in Young Adulthood

Abstract: Background and Purpose: There is a continuous rise in the prevalence of adolescent obesity and incidence of stroke among young adults in many Western countries, but the association between them is unclear. Methods: A nationwide population-based study of 1 900 384 Israeli adolescents (58% men; mean age, 17.3 years) who were evaluated before mandatory military service during 1985 and 2013. Body mass index was classified according to the US Center for Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…A population-based case–control study including 1,201 patients with ischemic stroke and 1154 controls aged 15–49 years showed that obesity defined as BMI > 30 kg/m 2 was associated with an increased risk (odds ratio, 1.57; 95% CI, 1.28–1.94) [ 29 ]. Additionally, a higher BMI in adolescents was associated with a greater risk of ischemic stroke [ 30 ]. The analysis of the Atherosclerosis Risk in Communities (ARIC) Study including approximately 13,000 black and white people showed that obesity was associated with a greater risk of ischemic stroke irrespective of race [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based case–control study including 1,201 patients with ischemic stroke and 1154 controls aged 15–49 years showed that obesity defined as BMI > 30 kg/m 2 was associated with an increased risk (odds ratio, 1.57; 95% CI, 1.28–1.94) [ 29 ]. Additionally, a higher BMI in adolescents was associated with a greater risk of ischemic stroke [ 30 ]. The analysis of the Atherosclerosis Risk in Communities (ARIC) Study including approximately 13,000 black and white people showed that obesity was associated with a greater risk of ischemic stroke irrespective of race [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many findings in the past suggesting that elevated BMI is associated with a higher risk of ischemic stroke (36)(37)(38)(39). However, the relationship between BMI and the prognosis of stroke patients is uncertain and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into obesity have yielded contrasting results. Some recent evidence suggests that obesity portends greater risks of IS within the young adult population with increasing body mass index yielding incremental increases in IS hazard [53][54][55]. However, other studies have found no significant association between obesity and stroke risk after controlling for other pertinent variables [55].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%